Transnational Exchange in the Nazi New Order: The Spanish Blue Division and its Medical Services. (October 2019) - Brydan, David
This article uses the case of the Spanish Blue Division to examine the history of transnational exchange and cooperation within the Nazi New Order. In particular, it explores the experiences of the Blue Division's medical services, which were required to engage most closely with the international environment of the Eastern Front. The Blue Division and its medical services shed new light on this topic in a number of different ways. Firstly, they show how the New Order was experienced by those from outside the core Axis states of Germany and Italy, and beyond the minority of ideologically-committed fascist fellow travellers. Secondly, volunteers within the medical corps help to illustrate how the New Order was perceived as a forum for scientific, intellectual and professional exchange, building on the traditional prestige of German science and pre-war practices of international scientific cooperation. Finally, integrating the perspectives of junior officers and rank-and-file troops helps to move beyond the political and cultural elites who dominate the literature on the New Order to show how cooperation and exchange worked on the ground. In particular, it demonstrates where the limits to this cooperation lay, and how individuals dealt with the tensions and conflicts between different national groups.